1955
DOI: 10.1037/h0048361
|View full text |Cite
|
Sign up to set email alerts
|

Displacement as a function of conflict.

Abstract: HE concept of displacement has long played an important role in the theory of neurosis. As early as 1894, Freud (2) said that phobias and obsessions were substitutes for unbearable sexual ideas. He saw sex as a form of energy which could be displaced from one idea to another, like an electric charge. This displacement mechanism operates in dreams (3) and in slips of the tongue (4). Hostile impulses, desires for prestige, and other nonsexual drives may also be expressed through displacement.The basic concept is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 8 publications
4
22
0
Order By: Relevance
“…These findings show how positive and negative evaluations of a goal can arise in an uncoupled manner through independent contingencies of reinforcement and punishment. In other studies (Miller, 1944;Murray & Berkun, 1955), the animals produced both reinforcement and punishment in the goal region, and they exhibited vacillatory behavior consistent with the approach and avoidance gradients that Brown measured separately. By inference, the strength of both tendencies increased as the animals got closer to the goal, an indication of coactive evaluative arousal (Cacioppo & Berntson, 1994).…”
Section: Bipolar Versus Bivariate Scales Of Right and Wrongsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings show how positive and negative evaluations of a goal can arise in an uncoupled manner through independent contingencies of reinforcement and punishment. In other studies (Miller, 1944;Murray & Berkun, 1955), the animals produced both reinforcement and punishment in the goal region, and they exhibited vacillatory behavior consistent with the approach and avoidance gradients that Brown measured separately. By inference, the strength of both tendencies increased as the animals got closer to the goal, an indication of coactive evaluative arousal (Cacioppo & Berntson, 1994).…”
Section: Bipolar Versus Bivariate Scales Of Right and Wrongsupporting
confidence: 65%
“…Another manifestation of the negativity bias is a tendency to avoid the setting in which conflict occurs. Murray and Berkun (1955) found that rats subjected to approach-avoidance conflict displaced their vacillatory behavior from the original runway in which they were shocked to adjacent, less threatening ones. In experiments on moral judgment, displacement would take the form of a bias toward making judgments of wrong against the action framed by the question, which in effect would increase the participant's psychological distance from the source of the conflict.…”
Section: Negativity Bias In Evaluative Activationsmentioning
confidence: 98%
“…gravitation), forces exerted by desired and avoided goals are inversely related to distance. Supporting goal gradients, enhanced motivation closer to the goal has been observed in several studies, with both animals and humans (e.g., Brown, 1948;Gjesme, 1974;Losco & Epstein, 1977;Miller & Kraeling, 1952;Miller & Murray, 1952;Murray & Berkun, 1955;Rigby, 1954;Smith, 1965).…”
mentioning
confidence: 91%
“…Displacement. A relatively weak person or object is blamed for the client's difficulties (Murry & Berkun, 1955). For example, a person may constantly express hostile feelings toward a submissive colleague while rarely criticizing an oppressive supervisor.…”
Section: The Operation Of Defense Mechanismsmentioning
confidence: 99%